Diaminoterephthalate–α-lipoic acid conjugates with fluorinated residues - Buschbeck, Leon; Markovic, Aleksandra; Wittstock, Gunther; Christoffers, Jens (Beilstein Journal of Organic Chemistry, 2019)
Two bifunctional diaminoterephthalate (DAT) fluorescence dyes were prepared in a three-step sequence including one deprotection reaction. One functional unit is α-lipoic acid (ALA) for binding the dye to gold surfaces. It was introduced to the DAT scaffold by an amidation reaction. The other functional unit is a para-(trifluoromethyl)benzyl group for facile detection of the surface-bound material by X-ray photoelectron spectroscopy (XPS). This residue was introduced by reductive amination of the DAT scaffold with the respective benzaldehyde derivative. In one compound (60% yield over three steps) the ALA unit is directly bound to the DAT as a relatively electron-withdrawing amide. In solution (CH2Cl2), this material shows strong fluorescence (quantum yield 57% with emission at 495 nm, absorption maximum at 420 nm). The other compound (57% yield over three steps) possesses a propylene spacer between the ALA and the DAT units for electronic decoupling, thus, bathochromic shifts are observed (absorption at 514 nm, emission at 566 nm). The quantum yield is, however, lower (4%). Self-assembled monolayers on a gold surface of both compounds were prepared and characterized by high-resolution XPS of the C 1s, O 1s, S 2p, N 1s and F 1s emissions. The high signal-to-noise ratios of the F 1s peaks indicated that trifluoromethylation is an excellent tool for the detection of surface-bound materials by XPS.
Keywords: chromophore; diaminoterephthalate; fluorine surface marker; fluorescence dye; lipoic acid; self-assembled monolayers

(untitled) - Liebermann, H. (Justus Liebigs Ann. Chem., 1914)

(untitled) - Christoffers, J. (Eur. J. Org. Chem., 2018)

(untitled) - Shimizu, M.; Asai, Y.; Takeda, Y.; Yamatani, A.; Hiyama, T. (Tetrahedron Lett., 2011)

(untitled) - Shimizu, M.; Fukui, H.; Natakani, M.; Sakaguchi, H. (Eur. J. Org. Chem., 2016)

(untitled) - Tang, B.; Wang, C.; Wang, Y.; Zhang, H. (Angew. Chem., Int. Ed., 2017)
Angew. Chem. 2017, 129, 12717–12721. doi:10.1002/ange.201706517

(untitled) - Sinnreich, J. (Synthesis, 1980)

(untitled) - Zhang, Y.; Starynowicz, P.; Christoffers, J. (Eur. J. Org. Chem., 2008)

(untitled) - Pflantz, R.; Christoffers, J. (Chem. – Eur. J., 2009)

(untitled) - Freimuth, L.; Christoffers, J. (Chem. – Eur. J., 2015)

(untitled) - Christoffers, J.; Freimuth, L.; Rozzi, C.; Lienau, C. (Synthesis, 2015)

(untitled) - Wache, N.; Schröder, C.; Koch, K.-W.; Christoffers, J. (ChemBioChem, 2012)

(untitled) - Wache, N.; Scholten, A.; Klüner, T.; Koch, K.-W.; Christoffers, J. (Eur. J. Org. Chem., 2012)

(untitled) - Wallisch, M.; Sulmann, S.; Koch, K.-W.; Christoffers, J. (Chem. – Eur. J., 2017)

(untitled) - Jewett, J. C.; Bertozzi, C. R. (Chem. Soc. Rev., 2010)

(untitled) - Wu, D.; Cheung, S.; Devocelle, M.; Zhang, L.-J.; Chen, Z.-L.; O'Shea, D. F. (Chem. Commun., 2015)

(untitled) - Haimi, P.; Sikorskaite-Gudziuniene, S.; Baniulis, D. (Proteomics, 2015)

(untitled) - Dietz, L.; Bosque, A.; Pankert, P.; Ohnesorge, S.; Merz, P.; Anel, A.; Schnölzer, M.; Thierse, H.-J. (Proteomics, 2009)

(untitled) - Ulman, A. (Chem. Rev., 1996)

(untitled) - Gooding, J. J.; Mearns, F.; Yang, W.; Liu, J. (Electroanalysis, 2003)

(untitled) - Wilbur, J. L.; Kumar, A.; Biebuyck, H. A.; Kim, E.; Whitesides, G. M. (Nanotechnology, 1996)

(untitled) - Ahn, Y.; Hong, S.; Jang, J. (J. Phys. Chem. B, 2006)

(untitled) - Li, Y.; Yuan, B.; Ji, H.; Han, D.; Chen, S.; Tian, F.; Jiang, X. (Angew. Chem., Int. Ed., 2007)
Angew. Chem. 2007, 119, 1112–1114. doi:10.1002/ange.200603844

(untitled) - Jadhav, S. A. (J. Mater. Chem., 2012)

(untitled) - Zhang, X.; Shi, F.; Niu, J.; Jiang, Y.; Wang, Z. (J. Mater. Chem., 2008)

(untitled) - Laibinis, P. E.; Whitesides, G. M.; Allara, D. L.; Tao, Y.-T.; Parikh, A. N.; Nuzzo, R. G. (J. Am. Chem. Soc., 1991)

(untitled) - Smalley, J. F.; Finklea, H. O.; Chidsey, C. E. D.; Linford, M. R.; Creager, S. E.; Ferraris, J. P.; Chalfant, K.; Zawodzinsk, T.; Feldberg, S. W.; Newton, M. D. (J. Am. Chem. Soc., 2003)

(untitled) - Eckermann, A. L.; Feld, D. J.; Shaw, J. A.; Meade, T. J. (Coord. Chem. Rev., 2010)

(untitled) - Bardea, A.; Katz, E.; Willner, I. (Electroanalysis, 2000)

(untitled) - Beulen, M. W. J.; van Veggel, F. C. J. M.; Reinhoudt, D. N. (Chem. Commun., 1999)

(untitled) - Hickman, J. J.; Ofer, D.; Laibinis, P. E.; Whitesides, G. M.; Wrighton, M. S. (Science, 1991)

(untitled) - Yang, W.; Gooding, J. J.; Hibbert, D. B. (Analyst, 2001)

(untitled) - Yang, W.; Jaramillo, D.; Gooding, J. J.; Hibbert, D. B.; Zhang, R.; Willett, G. D.; Fisher, K. J. (Chem. Commun., 2001)

(untitled) - Yang, W.; Gooding, J. J.; Hibbert, D. B. (J. Electroanal. Chem., 2001)

(untitled) - Gooding, J. J.; Erokhin, P.; Losic, D.; Yang, W.; Policarpio, V.; Liu, J.; Ho, F. M.; Situmorang, M.; Hibbert, D. B.; Shapter, J. G. (Anal. Sci., 2001)

(untitled) - Gooding, J. J.; Hibbert, D. B. (TrAC, Trends Anal. Chem., 1999)

(untitled) - Yousaf, M. N.; Mrksich, M. (J. Am. Chem. Soc., 1999)

(untitled) - Zhao, C.; Witte, I.; Wittstock, G. (Angew. Chem., Int. Ed., 2006)
Angew. Chem. 2006, 118, 5595–5597. doi:10.1002/ange.200601151

(untitled) - Lesch, A.; Vaske, B.; Meiners, F.; Momotenko, D.; Cortés-Salazar, F.; Girault, H. H.; Wittstock, G. (Angew. Chem., Int. Ed., 2012)
Angew. Chem. 2012, 124, 10559–10563. doi:10.1002/ange.201205347

(untitled) - Gooding, J. J.; Ciampi, S. (Chem. Soc. Rev., 2011)

(untitled) - Scofield, J. H. (J. Electron Spectrosc. Relat. Phenom., 1976)

(untitled) - Wu, Z.-Q.; Jiang, X.-K.; Zhu, S.-Z.; Li, Z.-T. (Org. Lett., 2004)

(untitled) - Penning, M.; Christoffers, J. (Eur. J. Org. Chem., 2012)

(untitled) - Hjelmgaard, T.; Faure, S.; Staerk, D.; Taillefumier, C.; Nielsen, J. (Eur. J. Org. Chem., 2011)

(untitled) - Buschbeck, L.; Christoffers, J. (J. Org. Chem., 2018)

(untitled) - Jimmidi, R.; Shroff, G. K.; Satyanarayana, M.; Reddy, B. R.; Kapireddy, J.; Sawant, M. A.; Sitaswad, S. L.; Arya, P.; Mitra, P. (Eur. J. Org. Chem., 2014)

(untitled) - Pachamuthu, K.; Zhu, X.; Schmidt, R. R. (J. Org. Chem., 2005)

(untitled) - Parker, C. A.; Rees, W. T. (Analyst, 1960)

(untitled) - Demas, J. N.; Crosby, G. A. (J. Phys. Chem., 1971)

(untitled) - Fery-Forgues, S.; Lavabre, D. (J. Chem. Educ., 1999)

(untitled) - Snare, M. J.; Treloar, F. E.; Ghiggino, K. P.; Thistlethwaite, P. J. (J. Photochem., 1982)

(untitled) - Casey, K. G.; Quitevis, E. L. (J. Phys. Chem., 1988)

(untitled) - Capitao, D.; Sahli, R.; Raouafi, N.; Limoges, B.; Fave, C.; Schöllhorn, B. (ChemElectroChem, 2016)

(untitled) - Desimoni, E.; Brunetti, B. (Chemosensors, 2015)

(untitled) - Gardella, J. A., Jr; Ferguson, S. A.; Chin, R. L. (Appl. Spectrosc., 1986)

(untitled) - Chinwangso, P.; Lee, H. J.; Lee, T. R. (Langmuir, 2015)

(untitled) - López, G. P.; Castner, D. G.; Ratner, B. D. (Surf. Interface Anal., 1991)

(untitled) - Spitzer, A.; Lüth, H. (Surf. Sci., 1985)

(untitled) - Zhang, X.; Ptasinska, S. (J. Phys. Chem. C, 2014)

(untitled) - Duwez, A.-S. (J. Electron Spectrosc. Relat. Phenom., 2004)

(untitled) - Laibinis, P. E.; Graham, R. L.; Biebuyck, H. A.; Whitesides, G. M. (Science, 1991)

(untitled) - Graham, R. L.; Bain, C. D.; Biebuyck, H. A.; Laibinis, P. E.; Whitesides, G. M. (J. Phys. Chem., 1993)

(untitled) - Heister, K.; Zharnikov, M.; Grunze, M.; Johansson, L. S. O.; Ulman, A. (Langmuir, 2001)

(untitled) - Han, M. G.; Im, S. S. (Polymer, 2000)